[4 + 3] and [4 + 2] mechanisms of the Diels-Alder reactions of vinylboranes: an analysis of the electron charge density distribution - Vallejos, Margarita (2013)
The Diels-Alder (DA) reactions of isoprene with vinylborane, dimethylvinylborane and dichlorovinylborane have been studied using density functional theory and the quantum theory of atoms in molecules. We evaluated the topological properties of the transition structures (TSs) and the evolution of such properties along the reaction paths. In accordance with previous studies, our results indicate that the endo TSs of the reaction with vinylborane present high [4 + 3] character, while the exo TSs and all the TSs of the reactions with dimethylvinylborane and dichlorovinylborane have [4 + 2] character. The higher charge concentration between the diene and the dienophile appears to account for the greater stabilization of the [4 + 3] TSs. The [4 + 3] structure turns into the [4 + 2] structure through a conflict mechanism in which the C1 and B atoms compete to become attached to C6. The C6?B interaction, present from early steps of the reaction until beyond the TSs, plays a key role in facilitating the formation of the new σ-bonds. The [4 + 3] and [4 + 2] mechanisms for the DA reactions of boron-substituted dienophiles may be distinguished by analyzing the profile of the ellipticity at the C1?C6 bcp along the course of the reaction.